Studies on Field Grafting and the Growth of the Grafts in Red Sanders - Kedhabnath, S.; Rawat, M. S.; Uniyal, D. P.; Lakshmikantham, D. (Indian Forester, 1976)
Grafts were successfully established in Red Sanders using cleft grafting method. The scions used were from 15 wavy grained trees showing different grades of waviness. The grafting work carried out in the month of March over two years gave an overall higher establishment as compared to that done in the month of February during three years. Comparison of rate of annual growth increment in the grafts showed that there was no significant difference between the clones in this character.